Organ donation and transplantation in the Russian Federation in 2021. 14th Report from the Registry of the Russian Transplant Society - S. V. Gautier; S. M. Khomyakov (Вестник трансплантологии и искусственных органов, 2022)
Objective: to monitor the current trends and developments in organ donation and transplantation in the Russian Federation based on data from the year 2021.  Materials and methods. Heads of organ transplant centers were surveyed through questionnaires. Data control was done using the information accounting system of the Russian Ministry of Health. We performed a comparative analysis of data obtained over years from various federal subjects of the Russian Federation and transplantation centers. Results. Based on data retrieved from the 2021 Registry, 45 kidney, 29 liver and 17 heart transplantation programs were existing in the Russian Federation as of the year 2021. The kidney transplant waiting list in 2021 included about 10.5% of the 60,000 patients receiving dialysis. Organ donation activity in 2021 was 4.5 per million population, with a 78.4% multi-organ procurement rate and an average of 3.0 organs procured from one effective donor. In 2021, there were 9.5 kidney transplants per million population, 4.2 liver transplants per million population and 2.0 heart transplants per million population. Same year, the number of transplant surgeries performed in the Russian Federation increased by 18.3% compared to the year 2020, reaching the level of 2019. In Moscow, organ donation activity was 23.7 per million population, that of 2019. In 2021, the city of Moscow and the Moscow region accounted for 12 functioning organ transplant centers, performing 57.7% of all kidney transplants and 70.5% of all extrarenal transplants in the country. The number of organ recipients in the Russian Federation has exceeded 140 per million population. Conclusion. In 2021, donor activity and volume of transplant care in Russian regions recovered. This was after the decline in 2020 that resulted from the new coronavirus disease (COVID-19) pandemic. In addition, 7 new transplant programs were established. Further development of regional organ donation and transplantation programs, improvement in their efficiency, increase in the activity of transplant centers and development of inter-regional collaboration are expected in the Russian Federation in 2022.